2008
DOI: 10.1021/jm701587d
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Characteristics for Solid-State Limited Solubility

Abstract: Solubility and solid-state characteristics were determined and multivariate data analysis was used to deduce structural features important for solid-state limited solubility of marketed drugs. Molecules with extended ring structures and large conjugated systems were less soluble, indicating that structural features related to rigidity and aromaticity result in solubility restricted by stable crystal structures. These descriptors successfully predicted the applied test set and can be useful for avoiding synthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
69
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 97 publications
(73 citation statements)
references
References 22 publications
(35 reference statements)
2
69
0
Order By: Relevance
“…These data are also provided for comparison in Table 2. [13][14][15][16] Agreement of this work with the literature for the most part is very good. The last column of the Table 3 reports the average values used in subsequent calculations.…”
Section: Fusion Enthalpies Of the Parabenssupporting
confidence: 71%
“…These data are also provided for comparison in Table 2. [13][14][15][16] Agreement of this work with the literature for the most part is very good. The last column of the Table 3 reports the average values used in subsequent calculations.…”
Section: Fusion Enthalpies Of the Parabenssupporting
confidence: 71%
“…2 Strategies to lock molecules in the correct binding conformation commonly involve rigidifying the molecule through the insertion of a ring system; however, this often results in decreased solubility, through increased lattice energy and predominantly increased logP. 22 The use of heteroatom insertion presented here may be seen as an alternative to cyclization to promote the required amide conformation without concomitant increase in clogP (Table S15). Ongoing research in our laboratory is focused on assessing the effect of conformational modulation on the biological activity of the 5-acyl-6,7-dihydrothieno[3,2-c]-pyridines.…”
Section: ■ Conclusionmentioning
confidence: 99%
“…This difference indicated that electrophilic substituents in the aromatic ring has a fundamental effect on the rate of deacylation. Compared with 2-chloro-N-arylacetamides bearing a benzene ring ( a The substrate(4 mmol) was treated with acetyl chloride (24 mmol) in the presence of 24 mmol K 2 CO 3 in acetone at room temperature b All products were identified by IR and 1 H NMR spectra c Yields refer to pure isolated products A facile and efficient method 81 [1][2][3][4][5][6][7][8][9][10][11][12], those with a aromatic heterocyclic ring (Table 8, entries 12-15) were, to some extent, less reactive and needed more than 3 h for completion of the reaction, but still afforded the corresponding products in excellent yields. We also found that both N-p-tolyl benzamide and N-benzyloxycarbonyl-benzamide could not be deacylated (not reported in this paper).…”
Section: Resultsmentioning
confidence: 99%